Experimental study on impact of iron coke hot briquette as an alternative fuel on isothermal reduction of pellets under simulated blast furnace conditions. (15th May 2020) - Wang, Hongtao; Chu, Mansheng; Bao, Jiwei; Liu, Zhenggen; Tang, Jue; Long, Hongming
Graphical abstract: Highlights: The interaction mechanism between the reduction of pellet and the gasification of ICHB within blast furnace is revealed. The improvement of ICHB for the reduction of pellet is enhanced with the temperature. The appropriate charging approach of ICHB into pellet is confirmed. The suitable charging ratio of ICHB in pellet is conducted. Abstract: Highly reactive iron coke hot briquette (ICHB) made by co-carbonizing the agglomerate of iron ore concentrate and blended coals is considered to be an alternative fuel to reduce carbon emission in a blast furnace through decreasing the temperature of the thermal reserve zone. The reduction process of iron-bearing burden is greatly significant for the smelting and smooth operation of blast furnace. In this study, the effects of ICHB on the reduction process of pellet were experimentally investigated under simulated conditions within a blast furnace, and the interaction mechanism between the gasification of ICHB and the reduction of pellet was revealed. The results showed that the reduction degree of pellet with mixing charging 10% ICHB is increased by 6.48% in comparison to that without adding ICHB and conventional coke. Furthermore, with increasing the temperature from 900 °C to 1100 °C, the reduction degree of pellet without adding ICHB is increased from 20.20% to 32.45%, while it is remarkably improved from 20.93% to 40.14% under the condition of mixed charging 10% ICHB. Moreover, with increasing the mixed ratio of ICHB from zero to 30%, the reduction degree of pellet evidently is accelerated from 23.69% to 33.72%, but the improvement in the reduction degree of pellet is levelled off as the charging ratio of ICHB is more than 20%, suggesting that the promotion has a limitation. The interaction mechanism is indicated that the gasification of ICHB and the reduction of pellet are mutually promoted through increasing the reducing potential in local region during the reaction process.